2015
DOI: 10.1371/journal.pone.0120990
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Adhesion Molecules, Pro-Inflammatory Cytokines and Cell-Derived Microparticles Contribute to Intima-Media Thickness and Symptoms in Postmenopausal Women

Abstract: Menopause, the cessation of menses, occurs with estrogens decline, low-grade inflammation, and impaired endothelial function, contributing to atherosclerotic risk. Intima-media thickness (IMT) is an early subclinical biomarker of atherosclerosis. Inflammation may have a role on symptoms: hot flashes, anxiety, and depressive mood, which also are related to endothelial dysfunction, increased IMT and cardiovascular risk. In this study we compared several inflammatory markers in early vs. late postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…As reproductive hormones rise and fall during the menstrual cycle in premenopausal women, corresponding changes in CRP occur [92]. During menopausal transition (i.e., perimenopause), women experience more pronounced hormonal fluctuations, subsequently resulting in diminished estrogen levels following menopause [91, 93]. Due partially to low estrogen levels, postmenopausal women experience elevated inflammation, which may affect women’s health during aging [9395].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reproductive hormones rise and fall during the menstrual cycle in premenopausal women, corresponding changes in CRP occur [92]. During menopausal transition (i.e., perimenopause), women experience more pronounced hormonal fluctuations, subsequently resulting in diminished estrogen levels following menopause [91, 93]. Due partially to low estrogen levels, postmenopausal women experience elevated inflammation, which may affect women’s health during aging [9395].…”
Section: Discussionmentioning
confidence: 99%
“…During menopausal transition (i.e., perimenopause), women experience more pronounced hormonal fluctuations, subsequently resulting in diminished estrogen levels following menopause [91, 93]. Due partially to low estrogen levels, postmenopausal women experience elevated inflammation, which may affect women’s health during aging [9395]. Indeed, estrogen typically inhibits inflammation, and inflammatory processes play a role in atherosclerosis, cardiovascular disease, and other age-related diseases later in life [94, 96, 97].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased CD11b levels have been associated with hypertension, a condition of high prevalence in the elderly population (Rea et al, 2013). Also, a study conducted with postmenopausal women showed a strong positive correlation of carotid intima-media thickness with CD11b expression and membrane-bound TNF-a (Figueroa-Vega et al, 2015), strengthening the connection between CD11b levels and pro-inflammatory parameters, leading to cardiovascular risk factors. Overall, increased CD11b is associated with higher adhesive response of stimulated neutrophils, even though the effectiveness of their migration and function may not be preserved with age (Wessels et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…CD11b has been associated with high-fat diet-induced obesity [37], and carotid intima-media thickness [38], and CD11b expression was described as lowest for non-classical monocytes after lipopolysaccharide stimulation [39] and in a rodent model of type 2 diabetes [40]. Results concerning CD36 atherogenicity are also contradictory since an increase [35] or deficiency [41] of its expression have been associated with the pathogenesis of atherosclerosis and CVD.…”
Section: Discussionmentioning
confidence: 99%